A Calcium-Calmodulin Antagonist Blocks Experimental Vibrio vulnificus Cytolysin-Induced Lethality in an Experimental Mouse Model - Lee, Young-Rae (American Society for Microbiology, 2004)
We demonstrated that trifluoperazine, a calcium-calmodulin antagonist, blocked the hyperpermeability induced by Vibrio vulnificus cytolysin in in vitro-modeled endothelium and prevented the deaths of mice. Furthermore, compared to tetracycline alone, tetracycline combined with trifluoperazine enhanced the survival rate of V. vulnificus-infected mice, indicating the role of the cytolysin as an important factor in pathogenesis.